Determining the Diffusivity of Nitrous Oxide in Soil using In Situ Tracers. Issue 1 (30th January 2014) - Shcherbak, Iurii; Philip Robertson, G.
Abstract : Diffusion is a key process for understanding the movement of nitrous oxide (N2 O), carbon dioxide (CO2 ), methane (CH4 ), oxygen (O2 ), and other biogeochemically important gases in soil. Soil gas diffusivity is highly variable, which makes the application of generic predictive models based on soil macrofeatures uncertain. In situ methods provide greater certainty but intensive sampling usually makes such determinations expensive. We compared single and inter‐port diffusivity determinations using a sparse sampling alternative. We used 28 in situ profile probes with ports at five depths for pulse sulfur hexafluoride (SF6 ) and N2 O tracer injections at single ports followed by two or three measurements in five adjacent ports at an agricultural site in southwest Michigan, USA. We repeated this procedure for three dates in the summer and two in the fall. In general, the sparse method provided accurate measurements of soil diffusivity. Estimated diffusivities of SF6 and N2 O had poorer agreement in the summer ( r 2 = 0.49) than in the fall ( r 2 = 0.96), likely due to less uniform soil moisture in summer. The low N2 O to SF6 diffusivity ratio (0.67 compared with 1.82 in free air) suggests that water solubility of N2 O plays a significant role in retarding its movement in the soil. Movement of the relatively insoluble SF6 is not obscured by dissolution in water making SF6 a superior tracer compared with N2 O. Median diffusivities in ports where the gas was injected were only moderately correlated ( r 2 = 0.45) with diffusivities at the same depth measured by the inter‐port method, likely due to an increase in the variability of diffusivity with distance from the injection port. Results show it is possible to estimate N2 O diffusivity with sparse measurements; accuracy can likely be further improved with knowledge of soil moisture and texture in the immediate vicinity of the injection and sampling ports, as uncertainty in water modeling is reduced.